STRATEGI KOMUNIKASI DALAM MENINGKATKAN PARTISIPASI PESERTA ( Studi Kasus Open Trip Seduluran Selawase Adventure dalam Pendakian Gunung Lawu) - Widowati, Laras; Hindra Hastuti, Nurnawati; Mahar Rizqi, Fikriana (Solidaritas, 2024)
This study aims to examine communication strategies in increasing participant engagement in the "Seduluran Selawase Adventure" open trip for the Mount Lawu expedition. The research uses a qualitative approach with the SMCRE (Source, Message, Channel, Receiver, Effect) model as the analytical framework. The focus of the study lies in the role of the source and message delivered during the event, rather than in the context of initial marketing or promotion. Data were collected through in-depth interviews and direct observation of the communication interactions between the organizers and participants. The results of the study indicate that the implemented communication strategy successfully increased participant engagement significantly. A credible source and clear, informative, and relevant messages to the participants' needs proved to be key factors in maintaining their involvement throughout the expedition. The study recommends enhancing the quality of communication, particularly in terms of the source and message, to improve participants' experiences in future events.